Assessment of Conflicts Management Strategies by Secondary School Principals - Moses Adeleke Adeoye (Universitas Pendidikan Indonesia (UPI), 2023)
Conflict management is the ability of the school head to deal with everyday situations in removing the cognitive barriers to agreement and flexibility. The principal has a compulsory task of utilizing and directing the behaviour of human resources of his school towards the accomplishment of the school goals. The study evaluates conflict management by secondary school principals. The study used a descriptive survey design with a population of 49 principals. Two research questions and one hypothesis were used to collect data. The review of the literature revealed that conflict is inevitable and inherent in every human organization. The research instrument used was titled ‘Assessment of Conflicts Management by Secondary Principals Questionnaire’ (ACMSPQ) with a 4-point scale. The questionnaire was divided into two sections, Section A entails the personal data of the respondents while Section B contains 17 items on assessment of conflicts management relating to staffs-related students’ related conflicts in secondary schools. The data were analyzed using a weighted mean for the two research questions at a benchmark level of 2.50 and a one-way analysis of variance for the hypotheses at levels of 0.5 level of probability. Findings from the data revealed that the assessment of conflict management by principals was effectively carried out through various strategies. It was concluded that principals should ensure the proper clarification of teachers’ roles or schedules of duties and the allocation of school resources to the staff.